Pre-service teachers’ blog reflections: Illuminating their growth and development - Rubén Garza; Shaunna F. Smith (Cogent Education, 2015)
Blogging, a mode of electronic journaling, has been identified as an effective means to help pre-service teachers to construct meaning about their experiences. The purpose of this study was to examine pre-service teachers’ reflections about their praxis through blogging and to describe the nature of their growth and development. The use of reflective writing through blogging helped to identify three themes that emerged from the data: (1) validation, (2) prescriptive, and (3) self-assessment. Our findings suggest that blogging facilitated a community of learners that provided support and encouragement. Pre-service teachers’ reflections revealed a focus on the mechanistic aspects of teaching without critically examining the nature of what was observed. However, our findings also suggest that structuring reflective thinking through blogging has the potential to foster a nascent understanding about teaching and learning.